aidez moo s il vous plaît j ai ça demain/Développer puis réduire, si possible, les
expressions suivantes :
A= 5x+4(2x+3) .B= (5x + 4) (2x+3)
C= (4x-5) x 2x+8 .D=(4x-5) (2x+8)​

Sagot :

Bonjour,

A= 5x+4(2x+3)=

5x+ 8x =12 =

13x +12

.B= (5x + 4) (2x+3)=

10x² +15x +8x +12=

1àx² +23x +12

C= (4x-5) x 2x+8 =

8x² -10x  +8

.D=(4x-5) (2x+8)​

8x² +32x -10x -40 =

8x² +22x -40

utilise * pour les multiplications

Réponse:

A = 5x+4(2x+3)

= 5x+8x+12

A = 13x + 12

B=(5x + 4) (2x+3)

= 10x^2+15x+8x+12

B= 10x^2+23x+12

C=(4x-5) x 2x+8

C= 8x^2-10x+8

D= (4x-5) (2x+8)

= 8x^2+32x-10x-40

D= 8x^2+22x-40

Voili voilou ;)